Palliative care in Primary Health Care: an integrative literature review - Thayná Champe da Silva; Elisabeta Albertina Nietsche; Silvana Bastos Cogo (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze scientific evidence on the implementation and performance of palliative care in Primary Health Care. Methods: an integrative literature review, according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, carried out in the PubMed, SciVerse Scopus and LILACS databases, in December 2020, without a time frame. Results: 22 original scientific articles were analyzed, 14 classified as evidence level VI. The objective was to understand the experiences and roles of professionals, patients and families on palliative care in Primary Health Care, articles focused on the theme of management and organization of health services and on the importance of educational interventions on the subject. Final Considerations: evidence found relating palliative care in Primary Health Care points to the possibility of this care; health teams work closely with the family and their home, but the need to expand this theme is still perceived.